Additional probiotic therapy lowers SCORAD index in children with atopic dermatitis - Ekaputri, Jessica; Evalina, Rita; Deliana, Melda (Faculty of Medicine, Trisakti University, 2016)
Background Atopic dermatitis (AD) is a common skin disease that is usually chronic, relapsing, causing pruritus and frequent in children. The pathogenesis of AD involves genetic, immunological and environmental factors causing skin barrier dysfunction and dysregulation of the immune system. Probiotic treatment has been claimed to offer several functional properties including stimulation of the immune system and plays an important role in AD. The objective of this study was to evaluate the effect of probiotic therapy on atopic dermatitis in children.Methods A randomized controlled trial was conducted on 62 children suffering from AD from December 2015 to January 2016. AD severity was assessed based on the scoring of atopic dermatitis (SCORAD) index. Subjects were divided into two groups consisting of 32 and 30 children, the probiotic (probiotic + emollient) and control (emollient) groups, respectively. SCORAD index was re-evaluated after 2 weeks of therapy. The data was analyzed using Mann Whitney test.Results After the intervention, the mean SCORAD index in the probiotic group was significantly much lower than the control group (18.09 Â± 8.59 vs 23.21 Â± 8.71; p=0.001). The mean decrease in SCORAD index in the probiotic group was 40.4 %, much higher than the control group 25.2%. The number needed to treat (NNT) score of probiotic treatment was 5.3.Conclusion The addition of probiotics to conventional therapy effectively lowers SCORAD index by 40.4% in atopic dermatitis. The impact of probiotics on SCORAD indices is thought to be attained by modification of the immunogenicity of potential allergens.